Education EDUKASI BIJAK KONSUMSI GARAM BERBASIS MEDIA ANIMASI GAMBAR BERPERSPEKTIF ḤIFẒ AN-NAFS UNTUK PENCEGAHAN HIPERTENSI PADA MASYARAKAT - Abrori; Syihabuddin Rafid Alwan Falah; Gusti M Aidil; Nur M Satria Ilman Rifada (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
Hypertension remains a major non-communicable disease with a high prevalence in Indonesia, largely driven by excessive salt consumption and low public awareness. This community service program aimed to improve knowledge, attitudes, and behaviors related to wise salt consumption through image-based animated edu       cational media integrated with the ḥifẓ an-nafs (preservation of life) perspective as a strategy for hypertension prevention. The program was conducted in Bangetayu Subdistrict, RT 06 RW 03, Semarang City, involving 67 participants representing community leaders, neighborhood officials, PKK and Posyandu cadres, LPMK members, religious figures, community leaders, and youth organizations. A participatory educational approach using image-based animation integrated health messages with ḥifẓ an-nafs values. Evaluation employed a pre-test and post-test design measuring knowledge, attitudes, and salt consumption behaviors, supported by baseline blood pressure screening. Educational effectiveness was analyzed using N-Gain scores. Baseline findings indicated a high proportion of participants with prehypertension (32%) and stage 1 hypertension (47%). Post-intervention analysis showed significant improvements in knowledge (N-Gain = 0.67), attitudes (N-Gain = 0.78), and salt consumption behaviors (N-Gain = 0.50). The greatest improvement was observed in participants’ understanding of ḥifẓ an-nafs, suggesting that integrating religious values enhanced message internalization, intrinsic motivation, and acceptance of healthy behaviors. Image-based animated education integrated with the ḥifẓ an-nafs perspective is effective in strengthening awareness and preventive behaviors related to hypertension and has strong potential as a community-based promotive–preventive health education model.